External gap progression after cyclic fatigue of adhesive overlays and crowns made with high translucency zirconia or lithium silicate. Issue 3 (16th November 2021) - Baldi, Andrea; Comba, Allegra; Ferrero, Giorgio; Italia, Edoardo; Michelotto Tempesta, Riccardo; Paolone, Gaetano; Mazzoni, Annalisa; Breschi, Lorenzo; Scotti, Nicola
Abstract: Objectives: To evaluate three‐dimensional external gap progression after chewing simulation of high translucency zirconia (HTZ) and zirconia‐reinforced lithium silicate (ZLS) applied on endodontically treated teeth with different preparation designs. Materials and Method: Endodontically treated molars were prepared with low‐retentive (adhesive overlay) and high‐retentive (full crown) designs above cementum‐enamel junction and restored with HTZ and ZLS. Micro‐computed tomography analysis was assessed before and after chewing simulation to evaluate three‐dimensionally the external gap progression. Results were statistically analyzed with two‐way ANOVA and post‐hoc Tukey test. Results: High‐retentive preparation design had a significantly inferior gap progression compared to the overlay preparation ( p < 0.01); ZLS exhibited a significant inferior gap progression compared to HTZ ( p < 0.01). Conclusions: High‐retentive preparations restored with ZLS seem to better perform in maintaining the sealing of the external margin after cyclic fatigue. Clinical significance: The clinician should pay attention to the proper combination of preparation designs and ceramic material selection for an endodontically treated molar restoration. HTZ seems to perform worse than lithium silicate in terms of marginal sealing, still showing lacks in resistance to cyclic fatigue when adhesive preparations are performed.